Lipid adsorption capacities of magnesium silicate and activated carbon prepared from the same rice hull - Taspinar, Ozgul O.; Ozgul-Yucel, Sevil (WILEY-V C H VERLAG GMBH, 2008)
This study is a comparison of the lipid adsorption capacities of synthetic magnesium silicate and activated carbon produced from rice hulls of the same origin. The lipids examined were the free fatty acids, diacylglycerols and monoacylglycerols of frying oils. Pure oleic acid, an unused sunflower frying oil and a used sunflower frying oil were used in the experiments. The produced adsorbents, magnesium silicate and activated carbon, have surface areas of 680 and 43 m(2)/g, respectively. The lipid adsorption capacity of the produced magnesium silicate was found as 644 mg polar compounds/g adsorbent and it is higher than the capacities of the industrial adsorbents, Magnesol XL and activated carbon. This value is only 368 mg polar compounds/g adsorbent for the activated carbon produced from the same-origin rice hull.
Keywords: activated carbon; adsorption; magnesium silicate; rice hull; FRYING OILS; ASH; REGENERATION; ADSORBENTS; Food Science & Technology; Nutrition & Dietetics